Analysis of Bakuok Lake Fishery Potential and its Zone in Kampar Regency, Riau Province - Novitri, Awinda; Kamal, Eni; Suparno, Suparno; Putra, Aprizon (Sumatra Journal of Disaster, Geography and Geography Education, 2020)
Fishery reserves are part of inland public waters in the form of lakes, swamps, rivers or protected puddles. The purpose of this study is to assess fisheries reserves based on social culture, analyze the suitability of locations and analyze zoning in Bokuok lake fishery reserves. The results of the socioculturalanalysis show that the fishery reserves are determined based on the system or customary law regulated in Ninik Mamak Decree No. 04/N.M/TB/IV/2014, have easy access to visit, have Pokmaswas who play an active role, have local wisdom that is Ma'awu activity. The results of the analysis of conformity, station I obtained a score of 75, classified as a fishery sanctuary functioning well and very effective. Station II obtained a score of 62 classified as fisheries asylum functioning well and is very effective. Station III obtained a score of 59 classified as fisheries asylum functioning moderately and quite effectively. The totalarea of Bokuok lake fishery reserves covers an area of 7.31 ha which is divided into 3 zones, the core zone with an area 1.63 ha, sustainable fishery zone with an area of 3.03 ha, utilization zone with an area of 2.65 ha.